L7SP: serviços para otimizar o gerenciamento e o desempenho de Blockchain Privados - Furtado, Fabricio Reis (Universidade do Vale do Rio dos Sinos, 2019)
Since the launch of the Bitcoin digital currency in 2009, the interest in blockchain technology has grown over the years and has attracted many researchers. The technology initially emerged within the Bitcoin platform to support operations with the digital currency in a decentralized and secure manner, without the need for intermediaries such as banks and government organizations. Due to its characteristics of decentralization and immutability, its potential was soon perceived for other application types, in addition to payments with criptocurrencies. Although changing some existing technology paradigms and providing several interesting benefits, blockchain technology also has some limitations and technical challenges compared to centralized systems, especially in terms of performance and scalability. Because it is a decentralized network, to validate transactions, blockchain needs to reach consensus among the different participating nodes. This feature is the main offender, because the protocols implemented to provide this securely distributed processing directly affect system performance. The limitations of scalability and performance of the blockchain are critical for public platforms such as Bitcoin, but also affect private networks, with the differential that they have greater autonomy in the solution setting. The private blockchain allows companies or groups of them to use the technology to validate internal transactions for different types of business applications. There are several proposals to improve the performance of the blockchain, however these proposals bring a series of changes difficult to implement and are not compatible with current applications. The current limitations prevent blockchain from being used on a large scale for other types of applications or even replace the currently known electronic payment forms, making studies necessary to address these gaps and evolve the technology. Considering this scenario of the need to improve the aspects covered by the blockchain and the opportunity to explore the technology for other applications in the corporate environment, this paper proposes the L7SP model that will be coupled to the private blockchain to provide performance and scalability gain and improve management of the system. L7SP is an intermediate layer that provides the stacking of services seeking faster transaction validation and block generation, performance monitoring and centralized management. The proposed model provides high availability and performance, generating resource savings, and maintaining the security and decentralization characteristics of the blockchain. The viability and effectiveness of L7SP is demonstrated through a prototype that acts among the validating nodes, being transparent to the clients that interact with the system and without interfering in the way the blockchain is implemented, being thus also compatible with the existing applications . L7SP runs on the AWS cloud and communicates with the other components of the solution using the protocols provided by the Multichain middleware, whose nodes also run in the cloud. The results of the introduction of L7SP and its services showed performance gains of 4 % to 422 % when compared to the performance of Multichain in its standard configuration. Tests with different parameterizations and workloads showed that load balancing with Round Roubin strategy and the use of data compression was the best combination to obtain the maximum performance gain. The efficient combination of these factors, with the introduction of new metrics and a more efficient system monitoring, configure the scientific contribution of this study.
Keywords: Blockchain; Escalabilidade; Desempenho; Blockchain; Scalability; Performance; ACCNPQ::Ciências Exatas e da Terra::Ciência da Computação